Cross-Sectional Investigation of Self-Reported Concussions and Reporting Behaviors in 866 Adolescent Rugby Union Players: Implications for Educational Strategies. (March 2020) - Beakey, Mark; Roe, Mark; Tiernan, Stephen; Keenan, Brian; Collins, Kieran
Abstract : Objective: To examine the self-recalled concussion and bell ringer (BR) prevalence, reporting rates, and reporting behaviors in adolescent rugby players. Design: Cross-sectional survey. Setting: School classroom. Participants: Adolescent male rugby players aged 12 to 18 years (n = 866). Main Outcome Measures: Concussion and BR prevalence, reporting rates, and reporting behaviors. Results: The sample reported a concussion and BR prevalence rate of 40% and 69.9%, respectively. Of these athletes with a history, 38.4% and 86.4% suffered recurrent concussions and BRs, respectively. The total reporting rates per 1000 suspected concussions and BRs were 474.8 [95% confidence interval (CI), 415.4-534.3] and 238.7 (95% CI, 217.8-259.5), respectively. The athletes highlighted several barriers which hindered their truthful reporting of concussion, including "not thinking the injury is serious enough to report" (70%), "wanting to win the game" (38%), and "not wanting to miss future games or training" (48%). Conclusions: Educational interventions are an invaluable component within a socioecological framework aimed at improving the concussion reporting rates of adolescent athletes. The self-recalled prevalence, underreporting rates, and behaviors of the sample are alarming, which prompts the need to further explore their motivational beliefs behind their decision to underreport a potential concussion. The information obtained can be used to tailor personalized interventions for specific athlete samples. Abstract : Supplemental Digital Content is Available in the Text.